Let's learn i.t : information technology - Diosdado G. Angeles Jr. (Quezon City : FNB Educational, Inc., 2020)
"Let's learn I.T is a book series intended to provide knowledge and a jumpstart on the skills in the basic of computer education. This book series has been created in order for the readers to acquire knowledge and skills that would be useful for any future career, not just in IT-related ones."
Includes bibliography.